Greek Topoi in the Lyrics of Branko Milkovic and Ivan Lalic, or on the Mediterranean Poetics of Svetlozar Igov - Lyudmila Mindova (Zeszyty Cyrylo-Metodiańskie)
The article analyses the work of prominent Serbian poets from the second half of the 20th century in the context of the Mediterranean tradition, referring to and further developing the research concepts and critical intuition of Prof. Svetlozar Igov (1945–2023). Thanks to this prominent translator and scholar of South Slavic literatures, the ideas and poetic imagery from neighbouring Balkan traditions and world culture became firmly established in the Bulgarian cultural space. This research focuses primarily on poets Branko Milkovic (1934–1961) and Ivan Lalic (1931–1996). Their works, translated into Bulgarian, open a unique access to the complex dimensions of the Mediterranean creative spirit. The analysis of source and translated texts lead to the conclusion that, especially with Milkovic and Lalic, Greek topoi appear not only in spatial and historical meanings, but also in vivid symbolism, which turns Hellas and the Mediterranean into metaphors of poetry and the literary world in general. Original title in Bulgarian: Гръцки топоси в лириката на Бранко Милкович и Иван Лалич, или за средиземноморската поетика на Светлозар Игов.